Commodity Outlook 2003: U.S. Cattle Livestock Market - Thomas E. Anton (EDIS)
This is EDIS document FE371, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published February 2003.